Lodovico Flori's Treatise on household accounting for the Jesuit Order (1636) : A Critical Translation - Sangster, Alan, (Early Modern History and Modern History E-Books Online, Collection 2025., 2026)
This is the first critical translation into English of Fr. Lodovico Flori's manual, published in 1636. Originally written in Sicilian-infused Italian for administrators within the houses and colleges of the Jesuit Order, it is widely considered to be an outstanding example of its type published before 1800. Its focus is the records of all transactions, the double entry method of bookkeeping adopted, and the organization of the accounting system. Its goal was to best serve the needs of the institutions of the Jesuit Order, while complying with the tenets, mores, and rules of the Order. It represents a landmark in the use of accounting technology in administration and management. Its use of accounting to serve administrative needs predicted how income and wealth are calculated today, predating commercial practice by over 100 years.